Implementation of Telemedicine in Health Services during the COVID-19 Pandemic in Developing Countries: Literature Review - Atika Puspa Irawati; Winny Setyonugroho (Jurnal Admmirasi, 2022)
Background: Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. This disease originated in Wuhan, China and continues to spread widely to other regions of the world. An important factor in slowing the transmission of the virus is limiting the social distancing possible by reducing person-to-person contact. The use of telemedicine technology is a twenty-first century approach. There are various advantages to using telemedicine technology, especially in non-emergency/routine care and in cases where the service does not require direct doctor-patient interaction. Objective: This study aims to determine the implementation of telemedicine in health services during the COVID-19 pandemic. Methods: The type of research is Literature review. Researchers searched data sources from various databases such as PubMed, SAGE journals , ScienceDirect and Mendeley. Article search in English and year of publication 2019-2022. The main keywords are using telemedicine, COVID-19, and developing countries . We summarize the articles included in the study in narrative form. There are 3 articles that meet the inclusion criteria. Result: The implementation of telemedicine in developing countries has several supporting and inhibiting factors. Factors supporting the sustainability of telemedicine implementation include easy access to health services for patients in areas that are difficult to reach conventional services, increased patient satisfaction, patient experience using telemedicine before, saving time for patients and health workers, saving costs from the patient side, improving service quality. The inhibiting factor is seen from the aspect of health workers, facilities/infrastructure, and patients. The telemedicine modalities discussed in the articles studied are smartphone-based and web-based telemedicine. Conclusion: The COVID-19 pandemic has encouraged the use of telemedicine in health services in many developing countries. The successful implementation of telemedicine in health services is influenced by supporting and inhibiting factors that require cooperation from various parties so that the implementation of telemedicine services can be even better.